The Effectiveness of the STEAM-based PBL Model in Understanding Basic Electrical Concepts among Vocational High School Students - Chusna, Chufadatul; Yoto, Yoto; Herwanto, Heru Wahyu (Lembaran Ilmu Kependidikan, 2024)
This research explores the effectiveness of the STEAM-based Problem-Based Learning (PBL) model in improving Vocational High School (SMK) students' understanding of basic electrical concepts. Through a literature review of 12 articles published since 2020, the study synthesizes findings on the integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) into PBL to promote deeper conceptual understanding and practical skills. The results show that the STEAM-based PBL model enhances student engagement, collaboration, and problem-solving skills by linking theory to real-life applications. This approach not only improves knowledge retention but also fosters the development of critical thinking and teamwork, which are essential for vocational students' success. The study concludes that this model is highly effective for vocational education, recommending its broader implementation to better prepare students for future challenges in technical fields. The novelty of this research lies in its focus on the combined application of STEAM and PBL in vocational education, providing a comprehensive approach to both theoretical and practical learning.